(untitled) (Research, Society and Development, 2021)
The evaluation that qualifies and classifies a particular concept or subject through pre-established standards can assume countless formats, meanings and purposes in the learning teaching process. Which path to choose? What to do with the results? How to deal with subjective feelings and opinions? How to standardize evaluative means in heterogeneous classes? Is it possible to measure a student’s performance using a numerical scale? There are numerous questions and, to study something so vast, we chose to conduct a systematic bibliographic research, seeking to compile studies of specialists on the subject. Through this research, the formal evaluation methods were considered to know the diversity of assessment instruments, the impressions that teachers and students have about them, their effectiveness and the place they occupy in the teaching-learning process. We grouped a set of researches by several theorists of immense academic property and credibility to understand, analyze and contribute to the enrichment of the theme, helping teachers, educational managers and researchers in the area of education to deal with the theme with greater theoretical foundation.